2009
DOI: 10.1186/1472-6785-9-17
|View full text |Cite
|
Sign up to set email alerts
|

Ecological niche partitioning between Anopheles gambiae molecular forms in Cameroon: the ecological side of speciation

Abstract: Background: Speciation among members of the Anopheles gambiae complex is thought to be promoted by disruptive selection and ecological divergence acting on sets of adaptation genes protected from recombination by polymorphic paracentric chromosomal inversions. However, shared chromosomal polymorphisms between the M and S molecular forms of An. gambiae and insufficient information about their relationship with ecological divergence challenge this view. We used Geographic Information Systems, Ecological Niche Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
295
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(326 citation statements)
references
References 80 publications
(173 reference statements)
26
295
3
2
Order By: Relevance
“…To confirm, we typed a subset of 288 specimens using species identification polymerase chain reactions (PCRs) (Fanello et al 2002;Santolamazza et al 2004) and found that each cluster comprised a single species. In agreement with previous surveys (Wondji et al 2005;Simard et al 2009), our collections indicate that the brackish water breeding An. melas is limited to coastal regions, whereas the arid-adapted An.…”
Section: Population Structure Of An Gambiae Sensu Lato Sibling Speciessupporting
confidence: 80%
“…To confirm, we typed a subset of 288 specimens using species identification polymerase chain reactions (PCRs) (Fanello et al 2002;Santolamazza et al 2004) and found that each cluster comprised a single species. In agreement with previous surveys (Wondji et al 2005;Simard et al 2009), our collections indicate that the brackish water breeding An. melas is limited to coastal regions, whereas the arid-adapted An.…”
Section: Population Structure Of An Gambiae Sensu Lato Sibling Speciessupporting
confidence: 80%
“…Indoor resting mosquitoes were sampled in September 2007 by insecticide spray sheet collection inside human dwellings, from seven villages spanning a latitudinal gradient from southern rainforest (3°52'N) to northern arid savanna (9°2 5'N) in Cameroon, Central Africa ( Figure 1; for a more detailed ecogeographic description, see Simard et al 2009). Specimens were preserved over desiccant in individual numbered microtubes.…”
Section: Population Sampling and Karyotypingmentioning
confidence: 99%
“…The frequencies of several inversions are positively correlated with aridity, such that frequencies peak and trough between dry and rainy seasons in a repeatable cyclical pattern (Coluzzi et al 1979;Rishikesh et al 1985;Petrarca et al 1990;Toure et al 1998). In addition, latitudinal clines of inversions in West and Central Africa run from mesic rainforest where the inversions are virtually absent, to xeric sahel where they are fixed, or nearly so (Coluzzi et al 1979;Simard et al 2009). Although the precise selective agents have not been established, thermal and desiccation stress are known threats to insects in arid environments (Gibbs 2002), and physiological tests on laboratory colonies of An.…”
mentioning
confidence: 99%
“…The M and S forms cannot be distinguished morphologically or by other specific phenotypic traits. However, general ecological differences are known (8)(9)(10)(11). The S form breeds in small ephemeral pools and puddles across sub-Saharan Africa, whereas the M form exploits larger, more stable breeding sites closely associated with agricultural or urban activity in West and Central Africa.…”
mentioning
confidence: 99%